1971
DOI: 10.1530/jrf.0.0240427
|View full text |Cite
|
Sign up to set email alerts
|

The `Sperm-Rise' Test

Abstract: After centrifugation of a mobile-sperm suspension, the spermatozoa will begin to move upwards from the sediment into the supernatant. This fact constitutes the background to the following method for comparative estimation of thè amounts of motility' in different test suspensions. The method is simple, adequately objective, and recordings can be made in parallel on several different test suspensions in which the spermatozoa have been in contact with various media for an identical time.Test suspensions containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0
1

Year Published

1972
1972
1991
1991

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…Bull spermatozoa were obtained from the cauda epididymidis of gonads from slaughtered bulls and collected in NaCl Ringer solution (see below) as in previous studies (Drevius, 1971a(Drevius, , 1972a.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bull spermatozoa were obtained from the cauda epididymidis of gonads from slaughtered bulls and collected in NaCl Ringer solution (see below) as in previous studies (Drevius, 1971a(Drevius, , 1972a.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of spermatozoa in different test suspensions was adjusted to 0-5% with the aid of the preliminary test described by Drevius (1971a). A sample (2-0 ml) of a given test suspension made up in isotonic, Ringer (see below) will, provided that the spermatozoa are immotile, give a spermatocrit of 0-010 ml when centrifuged for 15 min at 2000 g in tubes of the type described in Drevius (1971a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have used this method to measure the effect of caffeine on sperm motility. The stimulatory effect of caffeine was first demonstrated in epididymal (Drevius, 1971) and ejaculated (Garbers, First, Sullivan & Lardy, 1971) bovine sperms. Several studies (Bunge, 1973;Haesungcharern & Chulavatnatol, 1973;Schoenfeld, Amelar & Dubin, 1973;Levin et al, 1980;Makler et al, 1980) have shown a similar response in human sperms, although one study (Dougherty, Cockett & Urry, 1976) failed to confirm it.…”
mentioning
confidence: 99%